Two multifunctional organic-inorganic hybrid complexes based on polyoxometalates, BiEDTA and sodium linker: crystal structures, photochromic, and catalytic performances. Issue 14 (17th July 2016) - Teng, Chun-Lin; Xiao, Han-Xi; Cai, Qing; Tang, Jian-Ting; Cai, Tie-Jun; Deng, Qian
Abstract: Two 3-D organic–inorganic hybrid supermolecular complexes, Na(BiHEDTA·2H2 O)3 (PW12 O40 )·2H3 O (BiPW ) and Na(BiHEDTA·2H2 O)3 (PMo12 O40 )·2H3 O·2H2 O (BiPMo ) ethylenediamine tetraacetic acid (EDTA) have been synthesized by solution method and characterized by ultraviolet visible (UV–vis) spectroscopy, thermogravimetric-differential thermal analysis, photoluminescence, cyclic voltammetry, and single-crystal X-ray diffraction (XRD). XRD analysis reveals thatBiPW andBiPMo are isostructural with 3-D architectures assembled by 2-D layer tetranuclear cation and a Keggin-type polyoxoanion. Although these two hybrids exhibit similar structures, the properties depend on the nature of polyoxoanion [PM12 O40 ] 3− ( M  =  W, Mo). Under UV irradiation, BiPW andBiPMo show fast response of reversible and irreversible photochromism, respectively.BiPW exhibits excellent photocatalytic activity in degradation of methyl orange dyes under irradiation of UV–visible light. It can be reused for at least six cycles without obvious loss of activity in the degradation experiments;BiPMo shows catalytic activity in elimination of methanol. The elimination rate of methanol reaches 56.9% when the concentration of methanol is 2.3 g·m −3 and the flow velocity is 10 mL·min −1 at 100 °C. Abstract :